Down-regulation of proangiogenic microRNA-126 and microRNA-132 are early modulators of diabetic cardiac microangiopathy. Issue 1 (9th January 2017) - Rawal, Shruti; Munasinghe, Pujika Emani; Shindikar, Amol; Paulin, Jono; Cameron, Vicky; Manning, Patrick; Williams, Michael J.A.; Jones, Gregory T.; Bunton, Richard; Galvin, Ivor; Katare, Rajesh
Abstract : Aim: Microangiopathy due to endothelial dysfunction is a major contributing factor to the development of diabetes-induced cardiovascular disease (CVD). Dysregulation of endothelial-specific microRNAs (miRs) is correlated with impaired angiogenesis and cell survival. We investigated the profile of two angiomiRs, miR-126, and miR-132, in the plasma of type 2 diabetic individuals without any known history of CVD as well as in the cardiac tissues collected from diabetics undergoing cardiac surgery. Methods and results: The presence of diabetes alone significantly decreased both angiomiRs in the plasma and the myocardium. The down-regulation of angiomiRs was also associated with reduced capillaries and arterioles and increased endothelial cell apoptosis, the hallmark of microangiopathy. Importantly, a time course study in a type 2 diabetic mouse model confirmed that the down-regulation of angiomiRs preceded endothelial apoptosis as well as alterations in the density of the microvasculature. Finally, therapeutic overexpression of both angiomiRs in diabetic aortic rings and human umbilical vein endothelial cells exposed to high glucose (HG) abrogated the deleterious effects of diabetes and HG on cell survival and proliferation and restored their angiogenic potential. Conclusions: These novel findings demonstrate that the down-regulation of angiomiRs is a major underlying mechanism for the development of microangiopathy in diabetic hearts. Therefore, therapeutic restoration of angiomiRs could become a potential approach to combat the cardiovascular complications of diabetes.